1995
DOI: 10.1074/jbc.270.42.25001
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Ions Inhibit the Qp Center of Bovine Heart Mitochondrial bc1 Complex by Blocking a Protonatable Group

Abstract: . Zinc binds to a site which has the same affinity for zinc as for protons. We conclude that the zinc binding site is close to a protonatable group of the bc 1 complex with pK a ‫؍‬ 7.2 which has not been identified previously. We propose that this group is part of the proton channel at the hydroquinone oxidation center of the bc 1 complex.Inhibitors have been indispensable tools for elucidating the reactions of the ubiquitous bc 1 complexes (for a review, see Ref. 1). Almost all of these inhibitors are aroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
137
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(155 citation statements)
references
References 25 publications
18
137
0
Order By: Relevance
“…Skulachev et al (1967) found that μM free zinc ions inhibited electron transfer between cytochrome b and c 1 of complex III and had no effect on the cytochrome c oxidase; and our results are in general agreement with those observations. Similar observations were reported by studies in bovine heart mitochondria (Nicholls and Malviya, 1968;Kleiner and von Jagow, 1972;Lorusso et al, 1991;Link and von Jagow, 1995). Link and von Jagow (1995) proposed that zinc inhibits complex III by interfering with proton transfer reactions at the Q p center of the bc 1 complex.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Skulachev et al (1967) found that μM free zinc ions inhibited electron transfer between cytochrome b and c 1 of complex III and had no effect on the cytochrome c oxidase; and our results are in general agreement with those observations. Similar observations were reported by studies in bovine heart mitochondria (Nicholls and Malviya, 1968;Kleiner and von Jagow, 1972;Lorusso et al, 1991;Link and von Jagow, 1995). Link and von Jagow (1995) proposed that zinc inhibits complex III by interfering with proton transfer reactions at the Q p center of the bc 1 complex.…”
Section: Discussionsupporting
confidence: 84%
“…Similar observations were reported by studies in bovine heart mitochondria (Nicholls and Malviya, 1968;Kleiner and von Jagow, 1972;Lorusso et al, 1991;Link and von Jagow, 1995). Link and von Jagow (1995) proposed that zinc inhibits complex III by interfering with proton transfer reactions at the Q p center of the bc 1 complex. However, all these studies involved effects of free Zn + + ions, which do not exist in the intracellular environment.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In previous studies we have found that, on strong cytosolic loading, Zn 2ϩ is taken up into these organelles, from which it can be subsequently released in a Ca 2ϩ dependent fashion (10,11). Zn 2ϩ accumulation in mitochondria may not be benign, as Zn 2ϩ has been found to interfere with the function of isolated mitochondria (12)(13)(14)(15)(16)(17)(18)(19) and mitochondria are therefore likely to be sites at which this cation induces injurious effects on neurons (20,21).…”
mentioning
confidence: 99%